2004
DOI: 10.1242/dev.01378
|View full text |Cite
|
Sign up to set email alerts
|

Tbx2 is essential for patterning the atrioventricular canal and for morphogenesis of the outflow tract during heart development

Abstract: Tbx2 is a member of the T-box transcription factor gene family,and is expressed in a variety of tissues and organs during embryogenesis. In the developing heart, Tbx2 is expressed in the outflow tract, inner curvature, atrioventricular canal and inflow tract, corresponding to a myocardial zone that is excluded from chamber differentiation at 9.5 days post coitus (dpc). We have used targeted mutagenesis in mice to investigate Tbx2 function. Mice heterozygous for a Tbx2 null mutation appear normal but homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
272
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(283 citation statements)
references
References 61 publications
9
272
1
1
Order By: Relevance
“…The lor p25bbtl phenotype demonstrates many features opposite to those observed in enhanced S-cone syndrome and mutations of Nr2e3 or Nrl in mice. Genetic analysis revealed that lor p25bbtl is an allele of tbx2b, a T-box TF with essential roles in development (19)(20)(21)(22). Our data suggest that during photoreceptor cell differentiation, tbx2b acts cell-autonomously to promote the UV-cone fate by repressing the rod fate in zebrafish photoreceptor cell progenitors.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The lor p25bbtl phenotype demonstrates many features opposite to those observed in enhanced S-cone syndrome and mutations of Nr2e3 or Nrl in mice. Genetic analysis revealed that lor p25bbtl is an allele of tbx2b, a T-box TF with essential roles in development (19)(20)(21)(22). Our data suggest that during photoreceptor cell differentiation, tbx2b acts cell-autonomously to promote the UV-cone fate by repressing the rod fate in zebrafish photoreceptor cell progenitors.…”
mentioning
confidence: 72%
“…1G), where tbx4 and tbx2b/fby were localized (21). tbx2b is a TF mainly associated with transcriptional repression during cell cycle control, limb, heart and endoderm development (19,20,22), and cancer (25). A single mutant allele of tbx2b has been reported in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…6). In the mouse, Tbx2 distribution is also restricted to the dorsal retina and a knockout line has recently been reported in which cardiac defects were characterized (36). It will be interesting to examine the retinas of these embryos to determine whether Tbx2 plays a similar role in asymmetrically regulating retinal neuron differentiation in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, misexpression of Hand2, Gli3, and Shh are among the first events observed, further suggesting that Tbx3 lies upstream in the gene expression cascade involved in limb AP polarization. Tbx2 mutation, on the other side, leads to a digit 4 bifurcation (Harrelson et al, 2004). This finding may be more related to the role Tbx2 and Tbx3 play a role in local morphogenesis of digits downstream of the interdigital BMP signaling (Suzuki et al, 2004) The HoxD cluster plays a major role in digit formation, in conjunction with paralogous genes of the HoxA cluster.…”
Section: Role Of Tbx Genes In Specification Of More Posterior Identitymentioning
confidence: 99%